FACTORS INFLUENCING PROFESSIONAL IDENTITY DEVELOPMENT ON MEDICAL STUDENTS IN INDONESIA - Indah Puspasari Kiay Demak; Ria Sulistiana (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Professional identity plays a vital role for medical students, as it grows along with the year students spend time in faculty and the workplace. Professional identity allows a doctor to consider the medical code of ethics and behave professionally. This study aimed to explore factors influencing professional identity development on undergraduate medical students at Tadulako UniversityCase discussion: The case study was a qualitative study, that was conducted on the second, third and fourth year students, consisting of 18 students. The sampling technique used was purposive sampling. Data collection was carried out through focus group discussions using the Zoom meeting platform. The data obtained were analysed qualitatively by conducting a thematic analysis. The results obtained are the formation of professional identity occurs at the individual level, the relational level and the collective level. At the individual level, professional identity is influenced by factors of personal character, self-confidence, motivation, and belonging of the profession. At the relational level there is a peer factor. While at the collective level, there are factors of lecturers, organization, educational environment and systems, and learning methods.Conclusion: Most of the factors that influence professional identity development occur in the educational environment. Therefore, the faculty should be able to design curricula and make regulations to create an academic environment and atmosphere that can optimally support the formation of students' professional identities.